Development after globalization : theory and practice for the embattled south in a new imperial age - Saul, John S. (Three Essays Collective ; Zed ; UKZN Press ; Distributed in the USA by Palgrave, 2006)
John Saul suggests fresh ways to consider the dynamics of globalization, and seeks to rethink the ways of linking a class-based struggle with the progressive demands of gender equality and identity politics. He looks towards a synthesis of democratic, socialist, and anti-imperialist sensibilities and invites scholars and activists alike to involve themselves in the kind of intellectual activism that can underpin local, national, regional and global struggles.